Revenue Mobilization in Sub-Saharan Africa : Challenges from Globalization - Mansour, Mario (IMF Working Papers; Working Paper ;, 2009)
This paper evaluates the nature and extent of, and possible responses to, two of the central challenges that globalization poses for revenue mobilization in Sub-Saharan Africa (SSA): from corporate tax competition, and from trade liberalization. It does so using a new dataset with features needed to meaningfully address these issues: a distinction between resourcerelated and other revenues, and a disentangling of tariff from commodity tax revenue. Countries' experiences vary quite widely, nonresource revenues have been essentially stagnant. Corporate tax revenues have held up, despite a reduction in rates and evidence of substantial base-narrowing-something of a puzzle-and trade tax revenue reductions have been largely offset by other measures. Options for dealing with the continuation and intensification of the challenges, which the present crisis is likely to accelerate-including through regional cooperation-are discussed.